Impacts of dairy input and output price policy on producer incentives in Ethiopia - Staal, Steven J.; Shapiro, Barry I. (Ethiopian Society of Animal Production, 1995)
This paper desciribes dairy production and marketing in the Addis Abeba milk shed, and presents basic budgetary summaries of the components of the dairy system based on actual survey data. The budget results obtained from the farm, post-farm, and dairy system levels are first presented. Social valuation of output and inputs prices is then discussed. PAM matrices are then obtained for each system level and for the system as a whole, and the impact of specific public policy interventions is discussed. Comparative advantage and protection indicators are considered, and a sensitivity analysis of relative changes in some important parameters is presented.